EFEKTIVITAS WORKSHOP “ACADEMIC WRITING” DALAM MENINGKATKAN RESILIENSI AKADEMIK MAHASISWA SEMESTER AKHIR - Ika Apriati Widya Puteri (Faculty of Psychology Universitas Islam Sultan Agung Semarang, 2022)
Academic resilience is an individual's response to affective, cognitive, and behavioral in the face of academic difficulties or failures that he experienced. One of the efforts that can be done so that students have academic resilience is to provide preparation for thesis work. When students already have knowledge of thesis writing techniques, students can feel more prepared, so that they will grow a feeling of optimism in working on their thesis and confidence that they will be able to complete the thesis on time. The “Academic Writing” workshop is a series of workshops to provide knowledge and training to students regarding thesis writing. The themes that will be discussed in this workshop are how to make titles and raise research problems, thesis writing techniques, using reference manager applications, and various research methods. The purpose of this study was to determine the effectiveness of the